Neonatal Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The current concepts and revised classification of neonatal seizures are the subject of a special article from the Division of Pediatric Neurology, Washington University School of Medicine, St. Louis, MO.